THE EFFECT OF CAREER DEVELOPMENT AND JOB CHARACTERISTICS ON EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT - Hana Novie Eva Shinta; Lie Liana (SOSIOEDUKASI, 2026)
This study aims to analyze the effect of career development and job characteristics on employee performance mediated by organizational commitment. This study uses a quantitative approach with a population of 58 employees of the Wonosobo District BPPKAD. The data were processed using SPSS version 26 software. Data analysis techniques included respondent description, variable description, validity test, reliability test, F test, coefficient of determination (R2) test, t test, and Sobel Test. The results showed that career development had a positive effect on organizational commitment, job characteristics had a positive effect on organizational commitment, career development has a positive effect on employee performance, job characteristics have a positive effect on employee performance, organizational commitment has a positive effect on performance, organizational commitment mediates the effect of career development on employee performance, and organizational commitment mediates the effect of job characteristics on employee performance.